Accessibility of Shopping Malls for Mobility Impaired People in Jeddah - Shoman, Amna; Assiri, Wenas; Amba, Budoor; Aljohani, Dana; Alarfaj, Ahmad (J Med Rehab Sci, 2025)
Accessibility of mobility impaired people is an occupational therapy role in improving quality of life. Shopping malls are an essential part of entertainment venues that have to be accessible for a variety of individuals in the community. The objective of this study was to investigate the level of accessibility of shopping malls in Jeddah city, Saudi Arabia, aiming to improve the quality of life of people with physical disabilities. A total of 24 shopping malls as listed in Jeddah Municipality were included in this study. Senior occupational therapy students assessed accessibility of parking, routes, entrances, elevators, ramps, and restrooms for existing facilities using the Americans with Disabilities Act Checklist for Readily Achievable Barrier Removal. Statistical Package for the Social Sciences program was used to analyse data, and describe statistics into frequency and percentage. The findings showed 75% of Jeddah shopping malls were compliant. 90% was the highest score of two malls among twenty-four malls, while the lowest score was 55%. In particular, 79% of route statues were convenient to guidelines, and entrances fit 71%. Ramps indicated 63% compliance, whereas elevators showed 38% corresponding to parking, which had 33%. Restrooms were the minimum proper area with 14% score. Shopping malls in Jeddah need enforcement policies to improve accessibility and quality of life for individuals with mobility impaired.